Neuroregenerative property of haruan (Channa striatus spp.) traditional extract / Mohd Affendi Mohd Shafri, Abdul Manan Mat Jais and K. M. Kyu - Mohd Shafri, Mohd Affendi; Mat Jais, Abdul Manan; Kyu, K. M. (Universiti Teknologi MARA, Perlis, 2011)
Among key neurorestorative strategy in treating neurodegenerative diseases and brain trauma is neurostimulation using non-endogenous substances, thus improving regeneration and repair potential of neurons. The purpose of this work is to treat PC12 cells, an established neuronal differentiation model, with a traditional extract of haruan, Channa striatus spp, an indigenous riverine fish of Southeast Asian countries, and analyse PC12 cells’ morphologic and behavioural changes at different concentrations of the extract. PC12 cells were first cultured at 1x103 cells/cm2 density in 12 well plate in an incubator (5% CO2, 37°C), each containing 1ml of complete growth medium (Eagle’s Minimum Essential Medium with 10% foetal bovine serum), for 48 hours, to reach a 70% confluency. Media was removed and changed, and treated with 100µl, 200µl, 300µl and 400µl of haruan traditional extract (HTE). PC12 cells were observed under camera-equipped inverted microscope at 24, 48, 72 and 96 hours. Neurite outgrowth as well as growth behaviour were noted in comparison to negative (1ml complete growth medium) and positive (1ml cyclic AMP) controls. 100µl of HTE was demonstrated as the optimum concentration at which multiaxonal and multipolar cells and longest neurite outgrowth were seen. The result is suggesting that haruan traditional extract (HTE) is able to exert desirable effects in morphology and behaviour of PC12 cells and may potentially be useful therapeutically in the genesis and repair of neuron cells.